Discovery of CNS Penetrant CXCR2 Antagonists for the Potential Treatment of CNS Demyelinating Disorders - Xu, Heng (ACS Med Chem Lett, 2016)
[Image: see text] Structure–activity relationship exploration of the historical biarylurea series led to the identification of novel CNS penetrant CXCR2 antagonists with nanomolar potency, favorable PK profile, and good developability potentials. More importantly, the key compound 22 showed efficacy in a cuprizone-induced demyelination model with twice daily oral administration, thereby supporting CXCR2 to be a potential therapeutic target for the treatment of demyelinating diseases such as multiple sclerosis.